Satellite altimetry for geodesy, geophysics and oceanography : proceedings of the International Workshop on Satellite Altimetry, a joint workshop of IAG Section III Special Study Group SSG3.186 and IAG Section II, September 8-13, 2002, Wuhan, China [compact disc] - International Workshop on Satellite Altimetry ( 2002 : Wuhan, China); Hwang, Cheinway, 1962-; Shum, C. K.; Li, Jiancheng; International Association of Geodesy. Special Study Group (Berlin : Springer-Verlag, 2004)
PSZJBL